How concerned should we be about broiler breeder fertility declines? - Cara Cash; Kolton Witherspoon; Giridhar Athrey (Poultry Science)
Broiler breeder fertility is the bedrock on which modern broiler production rests. Over the last decade, fertility and hatchability issues have emerged as key topics of interest for both breeders and producers. In this study, we took an analytical approach to interrogate declining fertility trends among U.S. broiler breeders from 2013 to 2022, leveraging data from the USDA National Agricultural Statistics Service (NASS). Despite an increase in the number of eggs set and broilers raised to meet the rising demand for poultry, projections indicate that hatchability rates could decrease to approximately 60 % by 2050 without corrective action. Our Markov Chain Monte Carlo (MCMC) analysis reveals significant declines in essential production metrics, including hatchability, chick livability, and production efficiency. The analysis also includes 95 % credible intervals that confirm a persistent downward trend across these parameters. We developed the Broiler Breeder Performance Index (BBPI) to deepen our understanding of these trends, utilizing both Gaussian and Cauchy models to evaluate predictive performance. The BBPI projections suggest a decline below baseline values over time, underscoring the urgent need for interventions to counteract the fertility crisis in the broiler industry. Several factors contribute to this decline, including management practices and genetic selection strategies. Effective flock management techniques, such as sex-separate feeding and careful weight monitoring, are vital for improving reproductive viability among broiler breeders. Our findings highlight the necessity of addressing these fertility issues to ensure the long-term sustainability of U.S. poultry production. As the global demand for poultry meat grows, the poultry industry faces significant challenges in maintaining productivity. By pinpointing the causes of fertility decline and implementing effective management strategies, stakeholders can better navigate the complexities of poultry production and contribute to food security. This study aims to draw attention to the urgency of addressing broiler breeder fertility issues. It encourages further research into solutions that can enhance reproductive performance across various genetic stocks in the industry.